Experience experienced by people affected by COVID-19 in the route of hospital hospitalization (Research, Society and Development, 2021)
Objective: To analyze the experience of people affected by the new coronavirus in the course of hospitalization to discharge. Method: The data were analyzed using classical lexicographic analyzes at Iramuteq. The Descending Hierarchical Classification was obtained to measure the data of the dendrogram according to the classes generated, and finally, the Word Cloud, which unifies the words and displays them graphically according to their frequency. Results: The Descending Hierarchical Classification generated a general corpus consisting of 17 texts, separated into 79 text segments, with the use of 58STs (73.42%). The analyzed content was categorized into three classes: Class 1 (29.31%); Class 2 (34.48%) and Class 3 (36.21%). Conclusion: The experience of people affected by COVID-19 in the course of hospitalization to hospital discharge in the subjectivity and perspectives of each being was reported with different physical, emotional and social impacts that this pathogen causes in each individual.